Uses and applications of the red seaweed Kappaphycus alvarezii: a systematic review - Nunes, Aline [UNESP]; Azevedo, Gadiel Zilto; de Souza Dutra, Felipe; dos Santos, Beatriz Rocha; Schneider, Alex Ricardo; Oliveira, Eva Regina; Moura, Sidnei; Vianello, Fábio; Maraschin, Marcelo; Lima, Giuseppina Pace Pereira [UNESP] (Springer Nature, 2024)
Kappaphycus alvarezii is the fifth most cultivated macroalga in the world, with many industrial applications. Understanding the advances in research on K. alvarezii is essential to further biotechnological applications. Using PRISMA criteria a study was carried out on the CAPES Journals Portal database, between 2017-2023, with “Kappaphycus alvarezii” as single descriptor. Results (n = 559) were obtained and after defining the criteria, 152 manuscripts were subdivided into the following areas: cosmetics (n = 5), animal nutrition (n = 12), human food (n = 20), health/medicine (n = 33), agriculture (n = 34), and general industry (n = 48). From the results, the use of K. alvarezii biomass in the formulation of cosmetics for skin treatment and as a curative can be highlighted. Broad benefits were reported to humans and animals in food and feed supplementation. Moreover, in view of its bioactivities, certain metabolites have the potential to be used for developing new drugs due to their antitumor, antidiabetic, anti-inflammatory and neuroprotective activities. In agriculture, using various processes to make an extract, increases of plant yield and quality have been observed, reducing biotic and abiotic stresses and as a resistance elicitor. Kappaphycus alvarezii biomass has been used for producing biofuel and nanomaterials developments, and for the production of biofilms, especially for the food packaging industry. Thus, K. alvarezii presents wide industrial applications, not only due to the use of carrageenan. Therefore, it deserves further innovations, as it represents a matrix rich in bioactive compounds and is environmentally friendly, possibly replacing harmful ingredients currently used by industry.
Keywords: Agriculture; Cosmetic; Pharmaceutical; Rhodophyta; Seaweed